2015
DOI: 10.1016/j.euroecorev.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

International capital markets, oil producers and the Green Paradox

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…They found that increasing the size of the regulating coalition tends to reduce carbon leakage; however, they did not include a backstop technology. Van der Meijden et al (2015) also use a two-period general equilibrium model and divide the world into an oil importing and an oil-exporting region to investigate the macroeconomic effects of a future carbon tax on the interest rate, the relative wealth positions of the regions, and ultimately the green paradox. They focus primarily on the complete extraction case and do not incorporate technological change.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They found that increasing the size of the regulating coalition tends to reduce carbon leakage; however, they did not include a backstop technology. Van der Meijden et al (2015) also use a two-period general equilibrium model and divide the world into an oil importing and an oil-exporting region to investigate the macroeconomic effects of a future carbon tax on the interest rate, the relative wealth positions of the regions, and ultimately the green paradox. They focus primarily on the complete extraction case and do not incorporate technological change.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, Eichner and Pethig (2011), Van der Meijden et al (2015), and van der Ploeg (2016b) have shown that general equilibrium effects are likely to mitigate weak Green Paradox effects. The reason is that the front-loading of fossil supply increases current output relative to future output, which positively affects global savings and therefore drives down the interest rate.…”
Section: Carbon Leakage and The Green Paradoxmentioning
confidence: 99%
“…So far, most of the research on the conditions under which a green paradox occurs has used partial equilibrium analysis as, for example, in Edenhofer and Kalkuhl (2011), Gerlagh (2011), or van der Ploeg and Withagen (2012. Recently, this strand of research has been extended to general equilibrium models van der Meijden et al, 2014). Now, we are able to go even one step further.…”
mentioning
confidence: 92%